PENGARUH BERMAIN PERAN TERHADAP KEMAMPUAN MENGEKSPLORASI GERAK TARI PADA ANAK RAUDHATUL ATHFAL - Iswara, Indri Widia; Ghozali, Imam; Fretisari, Imma (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractEvery child is blessed with different potential abilities, however the ability off children needs to be optimized with learning process, one of which is role playing method in learning dance movements for early childhood. The problem in this study is how the effect of role playing methods on children's ability to explore dance moves in kindergarten Raudhatul Athfal Pontianak. The purpose of this study is to obtain information and to analyze the effect of role playing methods on children's ability to explore dance movements in kindergarten Raudhatul Athfal Pontianak. The method used in this study was an experimental method with quantitative research forms. The procedures of this study were the preparation stage, implementation stage and final stage. The source of data in this study were principals and teachers. The subjects used in this study were children in B1 class. Quantitative data was obtained through observation, preliminary research, and children's ability tests. The results of this study are the effect of role playing methods on children's ability to explore dance movements. There is a significant effect that occurs between pre-test and post-test. This assessment is based on indicators of children's exploration abilities, which are Flexibility, Originality, Elaboration, and Sensitivity.Â Keywords: Dance Movesï¼ŒExplorationï¼ŒRope Playing MethodÂ